Haiku Seven Gastronomicity - Kuttan, Sanjay (SARE: Southeast Asian Review of English, 2023)
Haiku is an unrhymed verse form of Japanese origin having three lines containing usually five, seven, and five syllables respectively, a poem in this form usually having a seasonal reference. I have always been searching for new ways to express myself and my recent collection of Haiku in ‘In One Breath’ was published in 2022. I chose to do seven Haiku to capture the various foods I enjoy covering a myriad of cuisines that reflect a very multicultural Singapore with multinational presence. Not that I am numerologist, but the number seven was particularly interesting because it consisted of the union of the physical (number 4) with the spiritual (number 3), and in Pythagorean numerology the number 7 means spirituality. Furthermore, as an early prime number in the series of positive integers, the number seven has also greatly symbolic associations in religion, mythology, superstition, philosophy and now in poetry as it reflects both the physical and spiritual nature of food. Food that unites and reunites relationships, always prepared with love and respect for the origins of the recipe and respect for the consumer as it becomes one with the body that enjoys its nourishment and teases the senses.